DOCUDRAMA GENRE TO REPRESENT RELIGIOUS EXPERIENCE IN OBAT MALAM AND SOLUSI TV PROGRAM: A CASE STUDY - Nopita Trihastutie (Lire Journal (Journal of Linguistics and Literature), 2022)
Genre is an important thing in planning film or TV program. This paper focuses on exploring two national TV programs that use docudrama genre to deliver people’s real past to represent their religious experience. By conducting interview with the producer of Obat Malam and Solusi TV program, the aim of this paper is to examine why docudrama genre used to represent religious experience in Obat Malam and Solusi TV program. The interview was conducted online via zoom meeting and involved the producer manager as the single participant. The open ended questions were used in the interview. A mix coding technique was applied in the interview data collection analysis. The findings show that producer’s perspective puts emphasis on docudrama genre as a configuration of particular elements, highlights visual narrative aspects, and accentuates qualities of docudrama modes of documentary. It can be concluded that docudrama genre meets the need of creative and contextual way to present religious experience to the viewers.